Upaya meningkatkan ketelitian dan kesabaran anak melalui bermain puzle usia 4-5 tahun di TK Aiyiah Bustanul Athfal - Tri Erlinda Febriyanti; Maimon Sumo; Dewi Pusparini (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstract: Accuracy and patience are one of the characteristics of children which can influence their cognitive development, considering that early childhood children have not yet stabilized their patience and accuracy characteristics, so they are given treatment by playing, one of which is playing puzzles. The objectives in this plan use pre-test and post-test. The data collection method in this research is based on observation and documentation. The data analysis method used in this research uses random sumpling, namely quantitative statistics. The independent sample test is used when carrying out data analysis. This shows a sig (2-tailed) value of 0.01. This can be seen when children are given educational games in the form of puzzles so that when playing children can develop the qualities of patience and accuracy in childrenKey words: accuracy and patience; puzzle; early childhood